The Gas Supply of Boston - Gray, John H. (Quarterly Journal of Economics, 1898)
Journal Article The Gas Supply of Boston Get access John H. Gray John H. Gray Northwestern University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 13, Issue 1, October 1898, Pages 15–44, https://doi.org/10.2307/1882981 Published: 01 October 1898